Neonatal MicroRNA Profile Determines Endothelial Function in Offspring of Hypertensive Pregnancies. Issue 4 (October 2018) - Yu, Grace Z.; Reilly, Svetlana; Lewandowski, Adam J.; Aye, Christina Y.L.; Simpson, Lisa J.; Newton, Laura D.; Davis, Esther F.; Zhu, Sha J.; Fox, Willow R.; Goel, Anuj; Watkins, Hugh; Channon, Keith M.; et al.
Abstract : Offspring of hypertensive pregnancies are at increased risk of developing hypertension in adulthood. In the neonatal period, they display endothelial cell dysfunction and altered microvascular development. MicroRNAs, as important endothelial cellular regulators, may play a role in this early endothelial dysfunction. Therefore, we identified differential microRNA patterns in endothelial cells from offspring of hypertensive pregnancies and determined their role in postnatal vascular cell function. Studies were performed on human umbilical vein endothelial cell samples from 57 pregnancies. Unbiased RNA sequencing identified 30 endothelial related microRNAs differentially expressed in human umbilical vein endothelial cells from hypertensive compared with normotensive pregnancies. Quantitative reverse transcription polymerase chain reaction confirmed a significant higher expression level of the top candidate, miR-146a. Combined miR-146a–targeted gene expression and pathway analysis revealed significant alterations in genes involved in inflammation, angiogenesis, and immune response in the same human umbilical vein endothelial cells. Elevated miR-146a expression level at birth identified cells with reduced ability for in vitro vascular tube formation, which was rescued by miR-146a inhibition. In contrast, miR-146a overexpression significantly reduced vascular tube formation in human umbilical vein endothelial cells from normotensive pregnancies. Finally, we confirmed that miR-146a levels at birth predicted in vivo microvascular development during the first 3 postnatal months. Offspring of hypertensive pregnancy have a distinct endothelial regulatory microRNA profile at birth, which is related to altered endothelial cell behavior and predicts patterns of microvascular development during the first 3 months of life. Modification of this microRNA profile in vitro can restore impaired vascular cell function. Abstract : Supplemental Digital Content is available in the text.